2017
DOI: 10.1093/nar/gkx208
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 promotes TERRA transcription and telomere protection upon heat stress

Abstract: In response to metabolic or environmental stress, cells activate powerful defense mechanisms to prevent the formation and accumulation of toxic protein aggregates. The main orchestrator of this cellular response is HSF1 (heat shock factor 1), a transcription factor involved in the up-regulation of protein-coding genes with protective roles. It has become very clear that HSF1 has a broader function than initially expected. Indeed, our previous work demonstrated that, upon stress, HSF1 activates the transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
(71 reference statements)
2
35
0
Order By: Relevance
“…Any sequence longer than 200 bp with more than 60% GC content was considered a CpG island. As seen in Figure 2B, roughly 75% of the analyzed chromosome ends contained CpG islands, in accordance with previously published data (Koskas et al 2017). Very strikingly, the up-regulation of TERRA correlated with the presence of CpG islands in the subtelomeric TERRA promoters (Fig.…”
Section: Quantification Of Terra Stemming From Different Chromosome Endssupporting
confidence: 92%
See 1 more Smart Citation
“…Any sequence longer than 200 bp with more than 60% GC content was considered a CpG island. As seen in Figure 2B, roughly 75% of the analyzed chromosome ends contained CpG islands, in accordance with previously published data (Koskas et al 2017). Very strikingly, the up-regulation of TERRA correlated with the presence of CpG islands in the subtelomeric TERRA promoters (Fig.…”
Section: Quantification Of Terra Stemming From Different Chromosome Endssupporting
confidence: 92%
“…The regulation of TERRA expression appears to be complex as it responds in addition to DNA methylation, to cell cycle progression, the telomeric DNA damage response, and telomere length (Porro et al 2010(Porro et al , 2014bArnoult et al 2012). A couple of transcription factors have been identified to regulate TERRA expression including CTCF, ATRX, NRF1, HSF1, Snail, and p53 (Deng et al 2012;Lovejoy et al 2012;Episkopou et al 2014;Eid et al 2015;Flynn et al 2015;Diman et al 2016;Tutton et al 2016;Koskas et al 2017;Mazzolini et al 2018). In a previous study, we identified the transcription start sites of multiple TERRA molecules as far as 5-10 kb upstream of the TTAGGG repeats.…”
Section: Znf148 Zfx Egr1 and Plag1 Repress Terra Expressionmentioning
confidence: 99%
“…In [166], 1) HeLa wild type cells (derived from cervical cancer cells), 2) human foreskin fibroblasts transfected with the catalytic subunit of the telomerase TERT (HFF2 cells) were the models of study. HSF1 knock-out cells were also included in the study.…”
Section: Upon Mildmentioning
confidence: 99%
“…In particular, it was shown in [166] that upon application of mild hyperthermia at 43˚C as a stress, HSF1 binds to subtelomeres (of the telomeres that contain heat shock elements) to trigger TERRA accumulation and protects the telomeres from the plausible accumulation of "telomericdysfunction-induced foci" (TIF) caused by stress exposure. In other words, the sub-telomeric DNA is found to be a new target of HSF1 with the physiological function of maintaining telomere integrity.…”
Section: Upon Mildmentioning
confidence: 99%
“…For this reason, TERRA molecules consist of subtelomere derived sequences at their 5′ end, and their 3′end includes arrays of UUAGGG repeats (reviewed in [8]). Expression of TERRA is tightly regulated by the activity of several transcription regulators, including the chromatin organizing factor CTCF [9] and the transcription factors heat shock factor 1 (HSF1) [10], Snail [11], as well as the nuclear respiratory factor NRF1 [12]. Furthermore, telomere shortening is associated with increased TERRA levels in yeast as well as human cells [13-16].…”
Section: Introductionmentioning
confidence: 99%